ChemInform Abstract: α‐Hydroxycyclopentanones via One‐Pot Oxidation of the Trimethylaluminum‐Mediated Nazarov Reaction with Triplet Oxygen. Issue 37 (16th September 2014) - Kwon, Yonghoon; Scadeng, Owen; McDonald, Robert; West, F. G.
Abstract A quick and convenient synthetic method to produce α‐hydroxycyclopentanones with three bond forming events via one‐pot interrupted Nazarov cyclization/oxidation using trimethylaluminum and triplet oxygen is described.